An Analysis of Chun Tao in The Sense of Survival - Ruomei, Fu (Humaniora, 2014)
In the novel "Chun Tao", Xu Dishan created Chun Tao as a new image of women, who has strong survival spirit, firm life philosophy and independent viability. Although Chun Tao?s life was full of suffering, she never gave up hope. Through the analysis of the survival consciousness of Chun Tao revealed her spirits of independent and self-respecting, also showed the glory of humanity distributed by Chun Tao. Through close reading to analyze the character Chun Tao from the perspective of survival, intend to provide a new angle of observation for the reader to understand Chun Tao.